Understanding the influence of online misogyny in schools from the perspective of teachers - Harriet Over; Carl Bunce; Jonathan Baggaley; David Zendle (PLoS ONE, 2025)
Young people are increasingly exposed to toxic online misogyny through social media. However, to date, it is not clear how exposure to online misogyny might be influencing the behaviour and experiences of adolescents and children. As a first step towards answering this question, we gathered data on how such influences are perceived by surveying 200 teachers, 100 of whom were based in secondary schools (working with children aged 11 and above) and 100 of whom were based in primary schools (working with children aged 4–11). 76% of secondary school teachers and 60% of primary school teachers reported that they were extremely concerned about the influence of online misogyny in their schools. When asked to describe an example of the ways in which online misogyny was influencing the behaviour and experiences of male pupils in their schools, teachers referenced cases in which male pupils praised misogynistic influencers, made misogynistic comments and engaged in discriminatory behaviour towards female peers and staff. When asked to describe an example of the ways in which online misogyny was influencing the behaviour and experiences of female pupils in their schools, teachers referenced cases in which female pupils were the victims of misogynistic behaviour and their well-being was adversely affected. 90% of secondary school teachers and 68% of primary school teachers felt that their school would benefit from dedicated teaching materials to address the impact of online misogynists within their schools. Implications of these data for interventions to combat the rise of online misogyny are discussed.